O infográfico enquanto gênero textual na revista Superinteressante: caracterização da estrutura do texto e da imagem - Marques, Elisângela Silvia Martins [UNESP] (2015)
Due to great possibilities of making use of technologies for the production of knowledge in today's society, foreign pedagogy school, the one proposed by the media, the scientific advancement and the growing interest of the population for scientific, aroused our interest for analysis infographics texts. These, featured in the journalistic sphere, have specific characteristics, whose goals involve the social, educational and placement of information to produce and clarify facts and events of interest to the public. The infographic, formed by the junction of words and images, has a dynamism whose main purpose is to make information more understandable to the reader. The Superinteressante magazine will serve as support for the study because it is a magazine that promotes scientific nature of matters, because it has a continuous use of this text and have a significant drawing. For the analysis, we ascertain the structure of the infographic supported in De Pablos categories by having theme, title, lead, source and signature, and we think this infographic is a text for its power to communicate; if this conveys as a genre, which in Bakhtin's perspective has theme, style and composition; to produce multiple meanings in will use the semiotics of culture, that is, the semiotics of texts, which allows us to infer the meanings of the text in the magazine. We note that the infographic has the potential to communicate and thinking in education, this language on the rise may make important contributions to knowledge acquisition